On non-associativity of Rhesus factor transmission - Ganikhodjaev, Nasir; Usmanova, Makhsuma (Eudoxus Press, LLC, 2011)
The Rhesus system is the second most significant blood group system in humanblood transfusion. Individuals either have, or do not have, the Rhesus factor(or Rh D antigen) on the surface of their red blood cells. A child inherits two rhesus genes, one from each parent, where gene D correspond to positive rhesus factor and gene d correspond to negative rhesus factor. The transmission of rhesus from parents to their offspring are random and events that contradict Mendel laws increase this randomness. To study this transmission we apply theory of quadratic stochastic operators and show that corresponding genetic algebra is non-associative.